Evaluation of Family Planning Village Program in Improving Family Welfare (Study on Paraikatte Village, Bajeng District, Gowa Regency - Haedar Akib; Dwi Hastuti; Muh Nur Yamin (Jurnal Aktor, 2024)
This study aims to find out how the results of the implementation of the Kampung KB program in improving family welfare and the impact of the Kampung KB program in Paraikatte Village. This type of research is descriptive qualitative research with data collection techniques in the form of interviews, observation and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of the implementation of the Family Planning Village program in Paraikatte Village in an effort to improve family welfare have referred to 8 family functions, but there are still obstacles in the field. This is because participation from the community is still lacking due to a lack of advocacy from field line officers and funds for activities are still lacking because they rely on community self-help and village funds. The impact of the Kampung KB program in improving family welfare in Paraikatte Village is still not optimal, seen from the increase in Pre KS + KS1, which means that the poor community still cannot be completed, so it can be concluded that the Kampung KB program is still not enough to be able to improve family welfare in Paraikatte Village.